An Analytical Hierarchy Process (AHP)-guided decision model for underground mining method selection - Gupta S.; Kumar U. (My University, 2025)
Decision making in mining, especially the selection of an appropriate stoping method for an ore deposit, is a critical and challenging task owing to its compliance with a set of criteria. The lack of quantitative data and the qualitative nature of the task forces one to adopt an experience- and intuition -based technique like the analytical hierarchy process (AHP). This article examines the application of the AHP for the selection of an appropriate stoping method from a group of alternatives. The developed model has been verified by a number of case studies. © 2012 Taylor & Francis.